Discovery of Tyrosinase Inhibitors: Structure-Based Virtual Screening and Biological Evaluation - Wang, Guan; Li, Jin; Pan, Xiao-Li; Bu, Fa-Qian; Zhu, Yu-Meng; Wang, Ao-Xue; Ouyang, Liang (Pharmaceutical Fronts, 2022)
Tyrosinase (EC 1.14.18.1) plays an indispensable role in the rate-limiting steps of melanin biosynthesis, and its uncontrolled activity may result in various diseases, such as albinism, melanoma, freckles, etc. The inhibition of tyrosinase activity may provide a useful and efficient strategy to treat hyperpigmentation disorders. However, the widely used tyrosinase inhibitors, like α-arbutin, hydroquinone, and kojic acid, have many shortcomings, such as lower efficacy and much more side effects. Herein, we reported the use of homology modeling and multistep structure-based virtual screening for the discovery of novel tyrosinase inhibitors. In this study, 10 initial potential hits (compounds T1–T10) were evaluated for enzyme inhibition and kinetic study, with kojic acid being used as a control. Among them, the IC50 values of both T1 (11.56 ± 0.98 µmol/L) and T5 (18.36 ± 0.82 µmol/L) were superior to that of kojic acid (23.12 ± 1.26 µmol/L). Moreover, T1 and T5 were also identified as the effective noncompetitive tyrosinase inhibitors by the subsequent kinetic study. Above all, T1 and T5 may represent the promising drug candidates for hyperpigmentation therapy in pharmaceutical fields, as well as the effective whitening agents in cosmetic applications.
Keywords: tyrosinase inhibitors; hyperpigmentation; homology modeling; virtual screening; kinetic study